Ambient Air Quality Perception of Embung’s Visitor in Institut Teknologi Sumatera - Alfian Zurfi; Firdha cahya alam; Fitralia Eliza (Journal of Multidisciplinary Academic, 2022)
Public open space or Urban open space as a means of outdoor activities are not only become part of the lifestyle but also the needs of the community especially for people who live in urban areas with a daily work routine. One of the public open spaces is the retention basin called Embung, where people carry out various activities both individually and in groups. Here, Institut Teknologi Sumatera (ITERA) as a state university located in South Lampung Regency Lampung Province has several Embungs from Embung A, B, C, D, E, and F. Embung A is the most frequently visit due to its position adjacent to the Terusan Ryacudu street that makes it easy to be accessed not only by ITERA academicians but also by surrounding communities in the morning and afternoon. However, this location which is close to a busy highway makes it potentially get negative impacts from transportation activities, one of which is air pollution. In this research aimed to determine the perceptions of the visitors about the ambient air quality in Embung A. Our research was carried out before the pandemic, more precisely in 2019. The results of the questionnaire found that most of the visitor consider the ambient air quality is in good condition (72%) with more than half of them (59% of the respondent) said that the Embung air quality were important. The statistical analysis results show a significant result (p-value=0.001 < 0.05) between perceptions of air quality with the duration of visits. In conclusion the Embung A visitors have a good perception of Embung’s ambient air quality and its importance. Further research is needed to better understand the motives behind the visit to Embung or other public open space and their relation to other environmental parameters.